Feasibility study for the Thelamork low-temperature system in N-Iceland - Bjornsson, Grimur; Axelsson, Gudni; Flovenz, Olafur G. (National Energy Authority, Grensasvegur, Reykjavik, IC, 1994)
The Thelamork low-temperature geothermal system in N-Iceland has for the last decade been considered as a possible source of hot water for the Akureyri District Heating Service. A productive well was drilled in the summer of 1992 afer 10 years of geothermal research in the area Following that a feasibility study was performed in order to determine whether harnessing the geothermal gwtem for space heating would be economical. This study consisted of a nine month full scale production test along with partial reinjection and tracer tests. It also involved careful monitoring of production rates, water level changes and chemistry. Finally, the data collected were analyzed on the basis of simple reservoir models. The results of the analysis indicate that the system will sustain a production of 19-20 I/s, initially at 91 degrees C, for the next 10 years, given that 3 l/s will be reinjected. However, a cooling of 9-12 "C is predicted due to infiltration of colder groundwater and the reinjection The results also suggest that hamessing the geothermal system will be economical, despite the high cost of exploration and an 11 km insulated pipeline to Akureyri.